A Descriptive Design of Farming Systems Components, Priorities, and Sociotechnical Packages towards Sustainable Intensification in Ethiopia - Wamatu, Jane; Ekule, Muluken; Dessalegn, Bezaiet; Frija, Aymen (2023)
The workshop was designed to gain a deeper understanding of the farming systems in Ethiopia that are of particular interest to the SI-MFS Initiative. This comprehension is crucial for creating tailored interventions that effectively tackle the unique challenges and opportunities presented by each farming system